Study of concentration and morphology of mechanoreceptors in the mucosa of uncinate process of the human nose - Adil S, Abd Alrazaq (2011)
To study the mechanoreceptors in the human nasal mucosa and to compare the mean concentration of mechanoreceptors in the Uncinate Process mucosa in patients with and without nasal polyp. Subjects were 12 adult patients; six participants in the study group (patient with nasal polyp) and six participants in control group (patients without nasal polyp). Both groups underwent functional endoscopic sinus surgery for their nasal pathology. During operation 1 x 1 em from the uncinate process mucosa was excised then fixed with formalin and sent to the pathology laboratory for staining, each sample was stained for Calretininlabeled antibody and Neurofilament- labeled antibody. After the staining process, the slides were examined by light microscope. There were no cells identified to be stained by Calretinin antibody in all 12 samples. However sample that stained with Neurofilament antibody showed the presence of the nerve terminals in the mucosa of all 12 samples. The mean concentration of nerve terminals was significantly higher in patients without nasal polyp (20.67±5.046) than for patients with nasal polyp (11.67±7.257). The results suggest that there are no specific cells in the nasal mucosa that act as mechanoreceptors. However the presence of the nerve terminals in the nasal mucosa and between the epithelial cells suggests that they are C-mechanoreceptors which are thought to be polymodal nerve terminals. In addition, reduction in the concentration of nerve terminals in patients with nasal polyp can be the reason for the reduction or absence of the feeling of nasal obstruction in some patients with nasal polyp.